Evidence for liver and peripheral immune cells secreting tumor-suppressive extracellular vesicles in melanoma patients - Lee, Jung Hyun; Eberhardt, Martin; Blume, Katja; Vera, Julio; Baur, Andreas (EBioMedicine, 2020)
Background: Before and after surgery melanoma patients harbor elevated levels of extracellular vesicles in plasma (pEV), suppressing tumor cell activity. However, due to technical reasons and lack of cell-specific biomarkers, their cellular origin remains obscure. Methods: We mimicked the interaction of tumor cells with liver cells and PBMC in vitro, and compared newly secreted EV-associated miRNAs and protein factors with those detected in melanoma patient`s pEV. Findings: Our results suggest that pEV from melanoma patients are secreted in part by residual or relapsing tumor cells, but also by liver and peripheral blood mononuclear cells (PBMC). Our approach identified factors that were seemingly associated either with tumor cell activity, or the counteracting immune system, including liver cells. Notably, the presence/absence of these factors correlated with the clinical stage and tumor relapse. Interpretation: Our study may provide new insights into the innate immune defense against tumor cells and implies that residual tumor cells could be more active than previously thought. In addition we provide some preliminary evidence that pEV marker patterns could be used to predict cancer relapse.
CRIS-Team Scopus Importer:2020-12-04
Keywords: Circulating tumor cells; Liver cells; Melanoma.; miRNA; Pev origin; Plasma extracellular vesicles (pev); Pro-inflammatory cytokines